2012
DOI: 10.4103/2278-960x.104293
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of gender and lipid profile with cardiac parasympathetic reactivity

Abstract: Background: Lower heart rate variability has been proven to be associated with a greater risk for developing hypertension among normotensive men, and hypertension is one of the major risk factor of coronary heart disease. Hormonal factors in premenopausal women may cause variance in heart rate variability and impact lipid profile. Objectives: The study was designed to evaluate the relationship of gender and lipid profile with cardiac parasympathetic reactivity. Materials and Methods: Sixty premenopausal and 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…This study showed that males have significantly higher percentage of abnormal HDL, LDL and TG compared to females. These results are consistent with that recorded by other authors both locally [ 12 ] and abroad [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…This study showed that males have significantly higher percentage of abnormal HDL, LDL and TG compared to females. These results are consistent with that recorded by other authors both locally [ 12 ] and abroad [ 21 ].…”
Section: Discussionsupporting
confidence: 94%